Geometrical modelling of braided textiles - Thompson, Matthew (2023)
Increasingly great pressures on design engineers to develop and manufacture lightweight and stiff structures can be seen across multiple industries. This has been achieved through the increase in the use of fibre reinforced composite materials. This is expected to continue with the added pressure of new and innovative solutions to such problems. Current trends have been towards using pre-impregnated woven or unidirectional fabrics with an increase in out-of-autoclave solutions being adopted. Alternative fabric geometries have been used in some small areas of the industry with examples of 3D woven and braided fabrics being used in some niche applications. Typically, the lack of use is due to the difficulty in the prediction and uncertainty surrounding the use of non-standard fabric architectures.